Adverse Outcome Prediction of Iron Deficiency in Patients with Acute Coronary Syndrome - Zeller, Tanja (Biomolecules, 2018)
Acute myocardial infarction remains a leading cause of morbidity and mortality. While iron deficient heart failure patients are at increased risk of future cardiovascular events and see improvement with intravenous supplementation, the clinical relevance of iron deficiency in acute coronary syndrome remains unclear. We aimed to evaluate the prognostic value of iron deficiency in the acute coronary syndrome (ACS). Levels of ferritin, iron, and transferrin were measured at baseline in 836 patients with ACS. A total of 29.1% was categorized as iron deficient. The prevalence of iron deficiency was clearly higher in women (42.8%), and in patients with anemia (42.5%). During a median follow-up of 4.0 years, 111 subjects (13.3%) experienced non-fatal myocardial infarction (MI) and cardiovascular mortality as combined endpoint. Iron deficiency strongly predicted non-fatal MI and cardiovascular mortality with a hazard ratio (HR) of 1.52 (95% confidence interval (CI) 1.03-2.26; p = 0.037) adjusted for age, sex, hypertension, smoking status, diabetes, hyperlipidemia, body-mass-index (BMI) This association remained significant (HR 1.73 (95% CI 1.07–2.81; p = 0.026)) after an additional adjustment for surrogates of cardiac function and heart failure severity (N-terminal pro B-type natriuretic peptide, NT-proBNP), for the size of myocardial necrosis (troponin), and for anemia (hemoglobin). Survival analyses for cardiovascular mortality and MI provided further evidence for the prognostic relevance of iron deficiency (HR 1.50 (95% CI 1.02–2.20)). Our data showed that iron deficiency is strongly associated with adverse outcome in acute coronary syndrome.